A large-scale screening of hepatitis C among men who have sex with men in the community using saliva point-of-care testing - Albertos, Sonia; Majo, Francesc X.; Esteban, Rafael; Colom, Joan; Buti, María (Frontiers in Public Health, 2024)
AimTo assess the feasibility and acceptability of massive hepatitis C virus (HCV) testing in point of care on the street using quick tests, determine the characteristics of the population included, and the prevalence of HCV infection in this population.MethodsCross-sectional community-based study including adult men who have sex with men (MSM) who attended the three most important LGTB+ events in Sitges (Catalonia, Spain) in 2022. Points of care were set up on tents on the street and attendees were offered voluntary anti-HCV antibody self-testing. Participants were informed of the study, provided consent, completed the test for identification of risk practices (TIRP), and took the test with the OraQuick® HCV test on a saliva sample (sensitivity: 97.8% [95% confidence interval (CI), 93.2–99.4%] and specificity: 100% [95% CI, 98.4–100%]; gold standard: IgG antibody test for HCV by immunoassay [serum]); participants with positive results were offered HCV virus testing with the Xpert HCV Fingerstick® on a blood drop.ResultsA total of 1249 adults participated in the large-scale screening, of which 1197 (95.8%) were identified as MSM. The screening time was 39 participants/h. Four (0.32%) participants had positive anti-HCV results, all with undetectable HCV RNA levels. Participants’ median (IQR) age was 44 (35, 54) years; most were Europeans, and 13% reported being unaware of their serological HCV status. The mean (SD) TIRP score was 1.40 (1.44) (n = 1062), with 67.41% reporting some risk, and the self-perceived sexually transmitted disease score was 3.0 (2.82) (n = 969).ConclusionThe point-of-care strategy on the street using a quick oral self-test at massive MSM events is feasible, well-accepted, and quick, and may be a useful strategy to reach other populations at risk of HCV infection.